Pengaruh Video Edukasi Pencegahan Diare Terhadap Pengetahuan, Sikap, Dan Motivasi Siswa Di Sekolah Dasar Negeri 215/Iv Kenali Asam Atas Kota Jambi - Gesin Junilza; Puspita Sari; Muhammad Rifqi Azhary; Usi Lanita; Andree Aulia Rahmat (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Diarrhea remains a common health problem among school-aged children due to limited knowledge, inadequate hygiene practices, and low motivation for prevention. This study aimed to examine the effect of diarrhea prevention educational videos on students' knowledge, attitudes, and motivation at SDN 215/IV Kenali Asam Atas, Jambi City. A quantitative quasi-experimental design with a one-group pre-test and post-test approach was employed. The study involved 58 fifth-grade students selected through total sampling. Data were collected using structured questionnaires before and after the educational intervention and analyzed using the Wilcoxon Signed Rank Test. The results showed significant improvements in knowledge, attitudes, and motivation following the intervention (p < 0.05). Mean knowledge scores increased from 6.00 to 9.27, attitude scores from 32.17 to 36.81, and motivation scores from 31.85 to 37.68. These findings indicate that educational videos are an effective health promotion medium for improving diarrhea prevention behavior among elementary school students.